World Bank Urban Transport Strategy Review : The Case of Cairo, Egypt - World Bank (Washington, DC, 2014)
The increased density and sprawl of Cairo's urban areas are the consequence of a number of factors, of which the major ones are the physical and geographic features, transport supply, urban policy and the control of urban development, market laws, government aid, property developers, consumer sensitivity to building quality and costs, travelling distances, tariffs, the immediate surrounding area, etc. The purpose of this study is to measure the impact of a transport policy on the accessibility and development of the Cairo urban area. Cairo's transport policy has encouraged tremendous development of major road infrastructures, partial liberalization of the surface public transport network resulting in a considerable expansion of private microbus lines, and an extension of the bus network at the expense of the density of supply and of regularity, and without creating segregated lanes as recommended in successive transport and urban studies, amongst other significant developments. This report explores the influence of transport on the development of urban areas, and the consequences of such developments.